INTERNALISASI APLIKASI MIND MAP PADA MEDIA PEMBELAJARAN GURU UNTUK MENINGKATKAN KOMPETENSI SISWA DALAM MEMPRODUKSI TEKS PROSEDUR - Patmawati Patmawati; Nurhayati Nurhayati; Ade Yolanda Latjuba (Universitas Hasanuddin, 2020)
This study aims (1) to explain the learning outcomes of Mind Map applications to improve the ability of Grade XI students of the Department of Network Computer Engineering at SMK Negeri 3 Makassar in producing procedure texts and (2) to explain and analyze the effectiveness of Mind map applications to improve the ability of SMK Negeri 3 Makassar students in producing procedure texts. This type of research is a class action or abbreviated with CAR. In this study there were no comparison classes. The experimental class as well as the control class. In its implementation several cycles are applied. The results showed: (1) An increase in student learning outcomes during the learning process took place with the learning of Mind map applications. Learning outcomes in the first cycle obtained an average value of 74.75 and the second cycle reached an average value of 84.06. Improved mastery learning outcomes classically is 31.25% with an average value of 9.31 and the final test score classically is 90.03. (2) With the Mind Mind application learning and teaching psychology approach to students, this proves that the mastery of learning to improve student competence in producing procedural texts has reached the specified KKM that is 75% and has been effective and the results are very good compared to learning with methods conventional.